Bina Nagari Pilubang Bersama Sosmas BEM KM UNP - putri nadia rizal nadia; hafizatul husna husna; Akbar Rafsanjani Akbar (Universitas Negeri Padang, 2022)
This community service was carried out in Nagari Pilubang, Padang Pariaman Regency. Geographically Nagari Pihole is located: to the north by Nagari Kuranji Hilir, to the east by Nagari Kuranji Hulu, to the south by Nagari V Koto, to the west by the Indonesian Ocean. This Nagari also has many MSMEs. So this service focuses on two issues, namely environmental and economic issues. In the social environmental issues activities, the community will plant various kinds of sea plant seeds, such as bayur tree seeds, sea cypress tree seeds, ketapang tree seeds. This is to help the community around the beach which is affected by abrasion. Meanwhile, in the economic aspect, the Ministry of Social Affairs will assist the Piuntung community to improve and develop MSMEs and the economy of the people there. The expected output target is to open people's awareness about how to get a PIRT number and halal certificate, to provide motivation to develop the quality of MSME products so that the marketing reach becomes broad by including the composition of the ingredients in the packaging including expiration date, PIRT number and halal certificate. Also, planting tree seedlings on the coast can help reduce the level of beach abrasion